2015
DOI: 10.1128/jcm.03556-14
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Mycobacterium avium subsp. silvaticum by Duplex High-Resolution Melt Analysis and Subspecies-Specific Real-Time PCR

Abstract: bAccurate identification of mycobacterial species and subspecies is essential to evaluate their significance and to perform epidemiological studies. The subspecies of Mycobacterium avium have different attributes but coincide in their zoonotic potential. Our knowledge about M. avium subsp. silvaticum is limited, since its identification is uncertain. Mycobacterium avium subsp. avium and M. avium subsp. silvaticum can be discriminated from each other based only on phenotypic characteristics, as they have almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In this regard, differentiation among MAP, MAA, M. intracellulare and MAS is achieved by specific PCR‐based identification using MAC‐specific gene targets (Ronai et al . ). However, in our study we demonstrated the possibility to identify the species belonging to MAC complex with MALDI‐TOF MS analysis.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In this regard, differentiation among MAP, MAA, M. intracellulare and MAS is achieved by specific PCR‐based identification using MAC‐specific gene targets (Ronai et al . ). However, in our study we demonstrated the possibility to identify the species belonging to MAC complex with MALDI‐TOF MS analysis.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, MAS, which shows some similarities to MAP for growth (both subspecies are mycobactin‐dependent and slow growing) (Ronai et al . ), but is almost identical to MAA in its genome (Ronai et al . ), clustered within the MAP group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations